Property crime distribution and equal police deployment - an empirical study of Taiwan - Tao, Hung-Lin (2004)
Police deployment and its associated base burglary level are derived based on the rule of a minimal national burglary level. Moreover, three rules of equality, namely, an equal number of burglaries, an equal crime rate, and an equal number of police per capita, are defined and their associated police deployments calculated. Data from Taiwan's 23 districts are used, and their respective base burglary levels are computed and compared with the minimal national burglary level and the actual level. - Reproduced.
Keywords: Property; Police; Crime